COVID-19 is not associated with worse long-term inflammatory bowel disease outcomes: a multicenter case–control study. (November 2022) - Hong, Simon J.; Bhattacharya, Sumona; Aboubakr, Aiya; Nadkarni, Devika; Lech, Diana; Ungaro, Ryan C.; Agrawal, Manasi; Hirten, Robert P.; Greywoode, Ruby; Mone, Anjali; Chang, Shannon; Hudesman, David P.; et al.
Background: Inflammatory bowel disease (IBD) is not associated with worse coronavirus disease 2019 (COVID-19) outcomes. However, data are lacking regarding the long-term impact of severe acute respiratory syndrome coronavirus 2 infection on the disease course of IBD. Objectives: We aimed to investigate the effect of COVID-19 on long-term outcomes of IBD. Design: We performed a multicenter case–control study of patients with IBD and COVID-19 between February 2020 and December 2020. Methods: Cases and controls were individuals with IBD with presence or absence, respectively, of COVID-19-related symptoms and confirmatory testing. The primary composite outcome was IBD-related hospitalization or surgery. Results: We identified 251 cases [ulcerative colitis ( n = 111, 45%), Crohn's disease ( n = 139, 55%)] and 251 controls, with a median follow-up of 394 days. The primary composite outcome of IBD-related hospitalization or surgery occurred in 29 (12%) cases versus 38 (15%) controls ( p = 0.24) and on multivariate Cox regression, COVID-19 was not associated with increased risk of adverse IBD outcomes [adjusted hazard ratio (aHR): 0.84, 95% confidence interval [CI]: 0.44–1.42]. When stratified by infection severity, severe COVID-19 was associated with a numerically increased risk of adverse IBD outcomes (aHR: 2.43, 95% CI: 1.00–5.86), whereas mild-to-moderate COVID-19 was not (aHR: 0.68, 95% CI: 0.38–1.23). Conclusion: In this case–control study, COVID-19 did not have a long-term impact on the disease course of IBD. However, severe COVID-19 was numerically associated with worse IBD outcomes, underscoring the continued importance of risk mitigation and prevention strategies for patients with IBD during the ongoing COVID-19 pandemic.